Ethical model of lobbying: An analysis of the codes regulating lobbying activity - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2019)
Self-regulation initiatives are undertaken by many lobbying circles in various countries. The key element of those initiatives are codes of ethics including a postulated model of lobbying activities, a specific pattern of ethical standards of lobbying. The aim of the article is a reconstruction of this pattern on the basis of the analysis of eight codes representing American, Polish, British, European and German lobbying. The analysis leads to the following conclusions. An axiological base of the lobbyist profession is created by such values as honesty, reliability, integrity, trust, professionalism, civic responsibility, openness, transparency, loyalty, respect, courtesy. Norms included in the codes are concentrated on the following issues: legality, transparency of actions, care of reputation and dignity of the profession, avoiding corruption, conflict of interest, customer relationship, duties toward society, public relations. A weak element of lobbying self-regulation is a system of norm execution.